An English Teacher’s Strategies in Implementing Computer Assisted Language Learning (CALL) in The EFL Classroom: A Case Study - Shelvia Refanda Mustika Putri (Fakultas Pendidikan, 2025)
The integration of technology in education, especially in English language teaching, is increasingly important in today's digital era because it is very effective in enhancing and developing skills. Computer-Assisted Language Learning (CALL) is one approach that utilizes computer technology to enhance the learning process. However, it is important to note that the success of CALL highly depends on how teachers implement it in actual classroom settings. This relates to the detail information regarding teaching strategies of English language teachers when implementing this approach in EFL classrooms, from preparation, implementation, to evaluation. Therefore, exploring how an experienced teacher implements CALL can provide valuable insights for broader implementation. This research aims to explore the strategies used by an experienced English teacher in applying the Computer-Assisted Language Learning (CALL) approach in the EFL classroom at a junior high school. The research also analyzed the media and activities used by the teacher during the process, and how students’ responses to its implementation. This research used a qualitative case study design. The research participant was an experienced English teacher at a junior high school in Banyuwangi who had been implementing CALL in his classroom for several years. Data were collected through preliminary observation and semi-structured interviews, which were then analyzed using thematic analysis to identify key themes and patterns related to teacher strategies, implementation, and student responses. This study identified three main themes: teacher strategies, CALL implementation, and student responses. Based on these findings, it was concluded that teachers in this study used a combination of several strategies, including meaningful learning, contextual learning, and multimodal learning. In implementing CALL, teachers also demonstrated through preparation by selecting easily accessible digital media and designing engaging classroom activities. Evaluation was conducted through creative and flexible assessments that allowed students to express themselves creatively and work independently. Students responded positively to the implementation of CALL, particularly through the use of multimedia such as images and videos. Students showed higher motivation, confidence, and participation in the learning process. In conclusion, the implementation of CALL by experienced teachers in this study, through a combination of well-planned, relevant, and adaptive strategies, supported by appropriate media and activities for students, resulted in positive responses to its implementation.
Reupload file repository 10 februari 2026 Maya/Mita
Keywords: Teacher’s Strategies in Implementing; Computer-Assisted Language